Integration of techno-pedagogical approach in English as a second language classroom: a systematic review - Leong, Lee Vun; Yunus, Melor Md; Ismail, Hanita Hanim (Institute of Advanced Engineering and Science, 2024)
The integration of technology in English as a second language (ESL) education is embraced by the educational institution and yet becomes a growing trend in today’s 21st century ESL classroom. The integration of techno-pedagogical approach in ESL classroom was critically examined in this systematic literature review by addressing three main research topics, the factors that ensure the effective integration of techno-pedagogical approach, yet the potential benefits and challenges of the implementation of this approach in ESL classroom. To review current studies, preferred reporting items for systematic reviews and meta-analyses (PRISMA) were adopted and two core journal databases, namely Scopus and Web of Science were utilized to review on 30 articles published in 2019-2023. A comprehensive overview that aids in understanding the intricate problems related to technology integration in ESL classrooms for educators and policymakers was provided and the delicate balance needed for integration to be effective, acknowledging the benefits and challenges of implementing techno-pedagogical approaches in ESL classroom was highlighted. Lastly, several recommendations that needed to be the subject of further investigation were made at the conclusion of this study.